Preservation Policy: A Challenging Task Both on a National and Local Level - Häkli, Esko (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
This presentation is an updated and edited version of a lecture which was given at the Preservation Management Summer School organized by the Nordiska vetenskapliga bibliotekarieförbundet (NVBF) in Mikkeli, Finland, June 18.-22., 2000.